Impact of COVID‐19 Pandemic on the Mental Health of Students From 2 Semi‐Rural High Schools in Georgia*. (12th April 2021) - Gazmararian, Julie; Weingart, Rachel; Campbell, Katherine; Cronin, Thomas; Ashta, Jasleen
ABSTRACT: BACKGROUND: Concerns have been raised about the consequences of the COVID‐19 pandemic on the mental health of adolescents during an important developmental and social period in their lives. This study examines the mental health impact of the pandemic on high school students shortly after closure of public schools in spring 2020, and whether this impact varies by sex, race/ethnicity, socioeconomic status (SES), and grade level. METHODS: A cross‐sectional, one‐time online survey was completed by racial/ethnically and socioeconomically diverse students in 9th through 12th grade at 2 semi‐rural Georgia public high schools (N = 761). RESULTS: Overall, almost one‐fourth of high school students were extremely or very worried about the pandemic, with higher rates of worry among students who are racial/ethnic minorities, lower SES, female and in older grades. Results indicated a concerning impact on the stress, anxiety, depression, and loneliness that students are feeling, particularly among girls and those in older grades. Students of color and low SES, who are already disproportionately impacted by COVID‐19, are also more likely to experience mental health challenges. CONCLUSIONS: Findings highlight important demographic differences of the impact of COVID‐19 on the mental health of high school students and have implications for schools with addressing these needs.